Developmental plasticity to desiccation risk in tadpoles of a tropical inselberg specialist - Delgadillo Méndez, Alexandra; Amézquita, Adolfo; Avellaneda Moreno, Mayra Alejandra; González-Arango, Catalina; Gomez-Mestre, Ivan (Frontiers in Ecology and Evolution, 2024)
Developmental plasticity evolves in heterogeneous environmental conditions as long as individuals can accurately perceive them. A paradigmatic example of developmental plasticity is the ability of amphibian larvae to alter growth and development in response to the risk of pond drying. Such responses are often found in amphibian species breeding in highly dynamic water bodies with high desiccation risk. The inselbergs of the Guianan Shield are rocky outcrops with extremely high and fluctuating temperatures and a marked seasonality in precipitation. During the rainy season, eroded depressions form precipitation-dependent pools with a high and variable risk of desiccation within the timeframe of a few days. The frog Leptodactylus lithonaetes specializes in breeding in this extreme environment, and its tadpoles are thus forced to cope with desiccation risk by adjusting their developmental trajectories and physiological performance. We experimentally assessed the effect of different levels of desiccation risk, under controlled temperature conditions, on developmental rate, growth, and temperature-dependent locomotor performance in tadpoles of Leptodactylus lithonaetes. We did not find an effect of desiccation risk on developmental rate, but under simulated drying conditions, tadpoles showed larger body size, greater body mass, and enhanced locomotor performance compared to constant (high or low) water levels. These results suggest that drying pools offer cues that trigger developmental and behavioral changes in these tadpoles, enabling them to enhance growth over a short time span without accelerating development. We discuss the potential compensatory mechanisms behind these responses and highlight the need for further investigations in species with semiterrestrial life histories in extreme environments.